If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3Xsquare + -13X + -10 = 0 Reorder the terms: -10 + -13X + 3aeqrsuX = 0 Solving -10 + -13X + 3aeqrsuX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '10' to each side of the equation. -10 + -13X + 10 + 3aeqrsuX = 0 + 10 Reorder the terms: -10 + 10 + -13X + 3aeqrsuX = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -13X + 3aeqrsuX = 0 + 10 -13X + 3aeqrsuX = 0 + 10 Combine like terms: 0 + 10 = 10 -13X + 3aeqrsuX = 10 Reorder the terms: -10 + -13X + 3aeqrsuX = 10 + -10 Combine like terms: 10 + -10 = 0 -10 + -13X + 3aeqrsuX = 0 The solution to this equation could not be determined.
| 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z | | y=x^2+m-4x | | 3*2+2=7*2-6 | | 2p+3-3p+8= | | a^2-6a+6=0 | | a^2-8a+b^2-2b+17=0 | | 9a^2-6a+b^2-2b+2=0 | | 35=-10+2x | | 3.7x=0.4 | | (12x^2)+(5x^2)+4x= | | 51+14x=x | | 4*(2x+3)-x*(4-x)=x*(x+1)+3*(x+4) | | 4xsquared-13x+9=-5x+6 | | 9-3k=0 | | 8t-14=0 | | 8m+3n-3m+10n= | | 48x^2-1537x-3076= | | 9x^2-2x^3=0 | | 3f^2+2f-f^2+4f= | | x^3+3x^2-8x+4=0 |